Green Architecture Approach to Integrated Laboratory and Greenhouse Design - Rismayadi, Hilman; Hermawan, Adhi; Aji, Sigit Wisnu (Dinasti Information and Technology, 2024)
The Green Architecture approach is a research theme in relation to environmental problems and global warming issues that affect building design. The purpose of this research using qualitative methods is to obtain design results with the Green Architecture concept and to highlight Acehnese architecture and Islamic architecture. Analysis is carried out on existing building data and interview results with users and stakeholders. The conclusion and suggestion are to obtain the design results of an integrated laboratory and greenhouse which aims to be a model that can be applied to similar buildings.